ISOLATION AND IDENTIFICATION OF SALMONELLA SPP FROM POULTRY MEAT SAMPLES (The Research of Medical Science Review, 2025)
Background: Poultry meat is a key source of contamination with Salmonella spp., which is the main cause of food-borne illness globally. Poultry is a major reservoir of salmonella infection and according to the CDC Salmonella is responsible for around one to two million annual cases of salmonellosis in the united state. Objective: To determine the prevalence of salmonella spp in poultry meat samples collected from different areas of district Swat Methodology: Our research study was conducted at the department of microbiology in government degree collage madyan swat from 05/11/2023to 05/05/2024. We collect the poultry meat samples in sterile polythene bags. A total of 120 poultry meat samples were collected from different chicken shops. All the samples were chopped by sterilized blades. Samples were enriched in buffered peptone water and then cultured on salmonella and shigella agar. All the culture positive samples were identified by microscopy and biochemical testing. All the data was collected in a pre-designed proforma. Data analysis was done by using SPSS version 24. Results: In the current study, a total of 120 meat samples from poultry shops of different areas of district Swat were process for the isolation and identification of salmonella spp. Out of 120 samples the salmonella spp positive samples were 60 (50%) while 60 (50%) samples were negative for salmonella spp. Thus the overall prevalence of salmonella spp in our study was 50%. Conclusion: Our study concludes that salmonella spp. is highly prevalent in poultry meat. Our study suggests the molecular level detection of salmonella associated with the poultry meat. The present research highlights the need of using appropriate storage, handling, and cooking techniques to avoid food-borne disease due to salmonella. The findings also emphasize the need for continued surveillance and implementation of effective interventions to reduce the risk of Salmonella contamination in poultry meat.